Analysis of the Contraction Stresses During the Polymerization Shrinkage of Bulk-fill Resin Composites and Nanocomposite by Finite Element Method - Thinson, Thitipong; Pholdee, Nantiwat; Sukjit, Kornkamon (Khon Kaen University Dental Journal, 2019)
This study aimed to analyze stress values in three dimensional (3D) solid model of mandibular first molar restored with four bulk-fill resin composite materials and one nanocomposite material using finite element method .A 3D solid model of mandibular first molar was designed using micro-CT data and SolidWorks software. Class II mesio-occluso-distal (MOD) cavity design was simulated. Four bulk-fill resin composites are Filtek™ Bulkfill Posterior Restorative) FBF), X-tra fil® (XF), SonicFill ) FS) and Tetric® N Ceram Bulk fill (TNB). For all 4 bulk-fill resin composites, the cavities were simulated to fill up with bulk technique. For one nanocomposite is Filtek™Z350XT (Z350). The cavity was simulated to fill up with 2 horizontal layers (2mm each) incremental technique. Polymerization shrinkage of resin composite materials were simulated by thermal analogy. Von-Mises stress in cavity, Maximum principal stress in adhesive layer and safety factor in adhesive layer were analyzed by descriptive statistics .This study found that cavities restored with bulk fill resin composites had Von-Mises stress and Maximum principal stress in adhesive layer higher than nanocomposite. Safety factor showed no debonding area in adhesive layer.